Prescaling and far-from-equilibrium hydrodynamics in the quark-gluon plasma - Mazeliauskas, Aleksas; Berges, Jürgen (Nuclear physics. A, Nuclear and hadronic physics, 2021)
We use the leading-order QCD kinetic equations with quarks and gluons to study the quark-gluon plasma in the far-from-equilibrium state. At weak coupling, we demonstrate the emergence of early hydrodynamic behavior—prescaling—around a nonthermal fixed point, which is qualitatively different from the more conventional hydrodynamics around equilibrium. Prescaling is a far-from-equilibrium phenomenon which describes the rapid establishment of a universal scaling form of distributions much before the universal values of their scaling exponents are realized. The dynamics in the prescaling regime is encoded in a few time-dependent scaling exponents, whose slow evolution gives rise to far-from-equilibrium hydrodynamic description.